Tuukkaq, Silamiut og Grønlands Nationalteater*: Antropologisk vending til ny-kontekstualiserte klassikere mytedramaturgi og inter-nordisk utveksling - Arntzen, Knut Ove (Peripeti, 2019)
Denne artikkelen tar for seg utviklingen av profesjonelt teater i Grønland på basis av Tuukkaq-tradisjonen og den antropologiske vending. Denne tradisjonen ble videreført i Silamiut-gruppen og senere Det grønlandske nationalteater og Teaterskolen i Nuuk. Teatrets betydning for dekolonisering av kulturlivet er også et viktig anliggende for artikkelen. This article gives an outline of the development of professional theatre in Greenland based in the Tuukkaq-tradition and the anthropological turn. is tradition was taken on by the Silamiut-company and later the Greenlandic National Theatre in Nuuk by and The Theatre School. Theatre’s impact on the decolonization of culture in Greenland is also an important statement.